Changement climatique et risques associés à la dégradation du permafrost : quels enjeux méthodologiques en ergonomie ? - Sandrine Caroly; Rafael Weissbrodt; Ludovic Ravanel; Xavier Bodin (Activités)
The aim of this article is to present a methodology for encouraging local stakeholders to cooperate on the prevention of an emerging risk. It concerns the degradation of mountain permafrost, which, with global warming, generates natural hazards (landslides, collapses, torrential lava) that create vulnerability for mountain professionals, public protection authorities and citizens living in the valleys. This methodology involves two steps. Firstly, an individual interview, based on intermediate objects (maps and real-life cases), leads the person into a reflective activity. This step prepares the way for the second step: the democratic workshop, where stakeholders discuss and exchange their needs on a regional level. The construction of this methodology, based on an interdisciplinary approach between ergonomics and geosciences, enables us to better grasp the stakes involved in the risk of permafrost degradation for those working in the field, in relation to their human activity and its evolution. It leads to a better understanding of phenomena in a given area, and to the development of preventive actions and social demand.